Defining the concept of innovation and firm innovativeness: A critical analysis from resource-based view perspective - Nur Fadiah Mohd Zawawi; Sazali Abdul Wahab; Abdullah Al- Mamun; Abu Sofian Yaacob; Naresh Kumar; Syed Ali Fazal (Canadian Center of Science and Education, 2016)
The primary objective of this paper is to contribute to the existing literatures by comprehensively reviewing the definitions, concept, as well as the importance of innovative and innovativeness in the business world. This review covers various definitions of innovation and innovativeness, multi dimensions of innovation and how this innovation acts to generate a good firm performance and competitive advantage, relying strongly on the famous Resource-Based View theory. Since the term ‘innovation’ itself is quite difficult to interpret, observe or evaluate, as argued by many scholars, this review attempts to provide discussion and enhance understanding on these concepts especially in the firm’s context. This review could shed some dynamic ideas for future researchers to further identify, conceptualize and understand the underlying theories and perspectives which strongly influence the previous, current and future concept of innovation.